2009
DOI: 10.1136/bcr.07.2008.0539
|View full text |Cite
|
Sign up to set email alerts
|

Remission of alcohol dependency following deep brain stimulation of the nucleus accumbens: valuable therapeutic implications?

Abstract: Chronic consumption of alcohol represents one of the greatest health and socioeconomic problems worldwide. We report on a 54-year-old patient with a severe anxiety disorder and secondary depressive disorder in whom bilateral deep brain stimulation (DBS) of the nucleus accumbens was carried out. Despite the absence of desired improvement in his primary disorder, we observed a remarkable although not primarily intended alleviation of the patient's comorbid alcohol dependency. Our case report demonstrates the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 13 publications
(11 reference statements)
0
77
0
7
Order By: Relevance
“…Fortuitous observations of improvements in alcoholism [125], nicotine [126][127][128] or food addiction [128] have been reported for patients treated with NAcc DBS for anxiety, OCD or GTS. Three patients were treated with NAcc DBS specifically for alcohol addiction.…”
Section: Reviewmentioning
confidence: 99%
“…Fortuitous observations of improvements in alcoholism [125], nicotine [126][127][128] or food addiction [128] have been reported for patients treated with NAcc DBS for anxiety, OCD or GTS. Three patients were treated with NAcc DBS specifically for alcohol addiction.…”
Section: Reviewmentioning
confidence: 99%
“…Based on this understanding, some functional neurosurgeons have used ablation or stimulation of the NAc to effectively treat severe refractory cases of obsessive-compulsive disorders and depression [11][12][13][14][15][16][17][18][19][20][21]. These patients incidentally noted decreases in chemical dependence [15][16]. In parallel, a series of Chinese animal studies suggested the utility of NAc lesioning in treating drug dependence [22], which led to initial trials in humans in China with reasonable efficacy [11].…”
Section: Introductionmentioning
confidence: 99%
“…The mesolimbic dopamine system plays a central role in brain reward mechanisms with the nucleus accumbens (NAc) serving as a key structure in mediating these effects [7][8][9][10]. Based on this understanding, some functional neurosurgeons have used ablation or stimulation of the NAc to effectively treat severe refractory cases of obsessive-compulsive disorders and depression [11][12][13][14][15][16][17][18][19][20][21]. These patients incidentally noted decreases in chemical dependence [15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, DBS has become an approved treatment option in OCD under the humanitarian device exemption, and current discussions aim to extend its therapeutic scope even further (Kuhn et al, 2010). Besides others, current approaches address addiction due to psychotropic substances and Alzheimer's disease, both representing disorders of great socioeconomic relevance (Kuhn et al, submitted;Kuhn et al, 2007;Laxton et al, 2010). However, all studies comprised a not neglectable number of non-responders.…”
Section: Introductionmentioning
confidence: 99%